FRI0709-HPR Levels of satisfaction with psoriatic arthritis (PSA) treatment and associated alignment between rheumatologists and their patients across latin america. (12th June 2018) - Zazzetti, F.; Soriano, E.R.; Rocio Gil, D.; Maldonado cocco, J.; Vega Morales, D.; Alves Pereira, I.; Guerra, G.; Bautista Molano, W.; Cassola, J.C.; Azevedo, V.; Aldunate, L.M.; Lobosco, S.
Abstract : Objectives: To assess levels of rheumatologist and patient satisfaction with PsA treatment across Latin America and any disconnects that may exist between the two in real world clinical practice. Methods: Data from the 2015 PsA Disease Specific Programme (DSP), a cross-sectional, multi-national survey of patients and rheumatologists conducted in Argentina, Mexico, Colombia and Venezuela were analyzed. Rheumatologists (n=141) completed forms containing patient demographics, patient disease severity and treatment satisfaction. Patients self-reported their level of treatment satisfaction and disease severity. Results: A total of 293 PsA patients from across Latin America were included in this analysis. Current mean age was 49.9 years and 48.1% were female. Proportions of rheumatologists and patients reporting satisfaction with treatment were both similarly high (84% and 92% respectively), however current disease severity reporting differed more markedly between rheumatologists and patients (mild 78%/moderate-severe 22% rheumatologists vs. 63% mild/37% moderate-severe patients; p=0.002). When assessed for alignment, 19% of all rheumatologists and patients disagreed on the level of treatment satisfaction; 13% of this was due to rheumatologists stating greater dissatisfaction than their patients, with the remaining 6% due to patients stating greater dissatisfaction than their rheumatologists (p=0.0543). For current disease severity, 32% of all rheumatologists and patients disagreed; 25% due to patients stating greater severity than their rheumatologists, with 7% due to rheumatologists stating greater severity than their patients (p<0.001). Of those patients for whom their rheumatologist was satisfied with treatment, 14% were classified as having moderate to severe PsA by that same physician. Conclusions: Despite many rheumatologists and their patients in Latin America reporting high levels of satisfaction with treatment, PsA patients can remain moderate to severe and disconnected from their physician. There is a need to improve physician/patient engagement as a means to improving clinical control. Disclosure of Interest: None declared